Investigations into the anti allergy properties of novel benzocycloalkanone based compounds - Woods, Orla (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2010)
An allergic response occurs because of a hypersensitive response by mast cells to an otherwise innocuous environmental substance. Allergen challenge causes mast cell degranulation, resulting in the release of mast cell mediators, including histamine, which interact with their receptors to induce the symptoms of allergy. Mast cell stabilising drugs inhibit the release of these mediators by preventing the activation of mast cells upon allergen challenge, while histamine receptor 1 (HIR) antagonists act at the HIR to prevent histamine binding. The primary aim of this project was to evaluate the mast cell stabilising activity of novel benzocycloalkanone-based compounds. Accordingly, these compounds were assessed in vitro using the rat peritoneal mast cell assay on Percoll-purified mast cells. Histamine release, elicited by incubating mast cells with calcium ionophore A23187 or compound 48/80, was quantified by fluorescence detection using o- phthaldialdehyde (OPT). Results indicate that several novel compounds assessed possess in vitro mast cell stabilising activity superior to that of disodium cromoglycate (DSCG), a commonly prescribed mast cell stabiliser.
Keywords: Pharmacy, Ph.D.; Ph.D. Trinity College Dublin